LITERACY AND LITERACY: : BIBLIOGRAPHIC REFLECTIONS ON THE PROCESS OF ACQUISITION OF READING AND WRITING IN AFROBETIZATION - Pereira Paulino, Patrícia (Revista Gênero e Interdisciplinaridade, 2022)
The present work discusses the themes of education and the teaching-learning processes of Youth and Adults throughout their lives, taking racial relations, Afrobetization and EJA in Brazil as a cut-out, considering what is determined by Law 10.639/03. This is a study that includes the analysis of indicators, bibliographical research and data from experiences in EJA, thought of in the light of Paulo Freire. The results reveal that Education for Young People and Adults, as it is mostly made up of black men and women, is basically an affirmative policy, which seeks to solve historical distortions and injustices. For this, the union of Afrobetization and literacy of (re)existences is pointed out.